Osteoinductive recombinant silk fusion proteins for bone regeneration. (February 2017) - Dinjaski, Nina; Plowright, Robyn; Zhou, Shun; Belton, David J.; Perry, Carole C.; Kaplan, David L.
Graphical abstract: Abstract: Protein polymers provide a unique opportunity for tunable designs of material systems due to the genetic basis of sequence control. To address the challenge of biomineralization interfaces with protein based materials, we genetically engineered spider silks to design organic-inorganic hybrid systems. The spider silk inspired domain (SGRGGLGGQG AGAAAAAGGA GQGGYGGLGSQGT)15 served as an organic scaffold to control material stability and to allow multiple modes of processing, whereas the hydroxyapatite binding domain VTKHLNQISQSY (VTK), provided control over osteogenesis. The VTK domain was fused either to the N-, C- or both terminals of the spider silk domain to understand the effect of position on material properties and mineralization. The addition of the VTK domain to silk did not affect the physical properties of the silk recombinant constructs, but it had a critical role in the induction of biomineralization. When the VTK domain was placed on both the C- and N-termini the formation of crystalline hydroxyapatite was significantly increased. In addition, all of the recombinant proteins in film format supported the growth and proliferation of human mesenchymal stem cells (hMSCs). Importantly, the presence of the VTK domain enhanced osteoinductive properties up to 3-fold compared to the control (silk alone without VTK). Therefore, silk-VTK fusion proteins have been shown suitable for mineralization and functionalization for specific biomedical applications. Statement of Significance: Organic-inorganic interfaces are integral to biomaterial functions in many areas of repair and regeneration. Several protein polymers have been investigated for this purpose. Despite their success the limited options to fine-tune their material properties, degradation patterns and functionalize them for each specific biomedical application limits their application. Various studies have shown that the biological performance of such proteins can be improved by genetic engineering. The present study provides data relating protein design parameters and functional outcome quantified by biomineralization and human mesenchymal stem cell differentiation. As such, it helps the design of osteoinductive recombinant biomaterials for bone regeneration.